New Regional Initiatives in China's Foreign Policy The Incoming Pluralism of Global Governance - Dian, Matteo (Springer International Publishing, 2018)
This book offers a theoretically informed study of recent Chinese initiatives to provide forms of regional economic governance; or as it is often termed in Chinese discourses, regional "public goods". It does so by considering the evolution of Chinese thinking on international relations and the global order, and by considering how the development of the Asian Infrastructure Investment Bank, the Belt and Road Initiative, and the putative Regional Comprehensive Economic Partnership reflect this change in thinking - and the change in both Chinese objectives and tactics. Matteo Dian is a Research Fellow at the School of Political Sciences at the University of Bologna, Italy. Silvia Menegazzi is Postdoctoral Research Fellow and Adjunct Lecturer in International Relations at the Department of Political Science, LUISS Guido Carli, Italy.